Peningkatan Kemampuan Berfikir Kritis Melalui Model Pembelajaran Kooperatif Tipe Group Investigation pada Mata Pelajaran IPS Di Sekolah Dasar - Indani Damayanti; Murni Winarsih; Deasyanti Deasyanti (EduBase : Journal of Basic Education, 2020)
This study aims to improve students' critical thinking skills in social science subjects in fifth grade students of SDN Majalengka Kulon I through the cooperative learning model type of group investigation. This study uses an action research method using the Kemmis and Mc.Taggart model which consists of four stages, namely, planning, action, observation and reflection which is carried out for two cycles. Data collection techniques using field notes, documentation, observation of teacher activities and observation of student activities, tests and non-tests. The subjects in this study were fifth grade students of SDN Majalengka Kulon I. The results showed an increase in critical thinking skills. This is evidenced by the average percentage of students in the first cycle of action that is 69.9%. Teacher activities according to the steps of this method reached 67.5% and student activities reached 65%. An increase in the second cycle reached 88% of teacher activity according to the steps of this method reached 90% and student activity reached 87.5%. The implication of this research is a group investigation cooperative learning model to improve critical thinking skills. In the teaching material theme 5 is proud as Indonesia. The results of this study indicate an increase in students' critical thinking skills through the cooperative learning model group investigation type. Keywords: Critical Thinking Ability;Model Group Investigation ; Action Research. Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan berpikir kritis siswa dalam mata pelajaran ilmu pengetahuan sosial pada siswa kelas V SDN Majalengka Kulon I melalui model pembelajaran kooperatif tipe group investigation. Penelitian ini menggunakan metode penelitian tindakan dengan menggunakan model Kemmis dan Mc.Taggart yang terdiri dari empat tahap yaitu, perencanaan, tindakan, observasi dan refleksi yang dilakukan selama dua siklus. Teknik pengumpulan data menggunakan catatan lapangan, dokumentasi, observasi aktivitas guru dan observasi aktivitas siswa, tes dan non tes. Subyek dalam penelitian ini adalah siswa kelas V SDN Majalengka Kulon I. Hasil penelitian menunjukan adanya peningkatan kemampuan berpikir kritis. Hal ini dibuktikan dengan rata-rata presentase siswa pada tindakan siklus I yaitu 69,9 %. Aktivitas guru sesuai langkah-langkah metode ini mencapai 67,5% dan aktivitas siswa mencapai 65%. Mengalami peningkatan pada siklus ke II mencapai 88% aktivitas guru sesuai langkah-langkah metode ini mencapai 90% dan aktivitas siswa mencapai 87,5%. Implikasi dari penelitian ini adalah model pembelajaran kooperatif tipe group investigation untuk meningkatkan kemampuan berpikir kritis. Pada meteri ajar tema 5 bangga sebagai Indonesia. Hasil penelitian ini menunjukan adanya peningkatan kemampuan berpikir kritis siswa melalui model pembelajaran kooperatif tipe group investigation. Kata Kunci: Kemampuan Berpikir Kritis; Model Group Investigation ;Penelitian Tindakan.